Percentages of PD-1+CD4+T cells and PD-L1+DCs are increased and sPD-1 level is elevated in patients with immune thrombocytopenia. Issue 4 (3rd April 2018) - Wang, Yingying; Pang, Nannan; Wang, Xinyou; Liu, Ying; Wang, Xiujuan; Wang, Lei; Sun, Mingling; Yasen, Halida; Zhao, Fang; Fan, Wenxia; Guo, Xinhong; Ding, Jianbing
ABSTRACT: The present study is to measure the expression of programmed death (PD)-1 / programmed death ligand-1 (PD-L1) negative costimulatory molecules, soluble format sPD-1 in patients with immune thrombocytopenia (ITP), and to investigate their correlation with the secretion of cytokines. A total of 35 patients with ITP were included in the present study. Twenty healthy subjects who received physical examination at our hospital were included as control group. Peripheral blood was collected from all ITP patients and healthy subjects. Flow cytometry was performed to determine the percentages of PD-1 + CD4 + T cells and PD-L1 + DCs in ITP patients and healthy subjects. Enzyme-linked immunosorbent assay was performed to measure the concentrations of interferon (IFN)-γ, interleukin (IL)-17 and sPD-1 in peripheral blood from ITP patients and healthy subjects. Percentages of PD-1 + CD4 + T cells and PD-L1 + DCs in peripheral blood from ITP patients before treatment were significantly higher than that from healthy subjects, but were not different from those after treatment. Serum concentrations of IFN-γ, IL-17 and sPD-1 in ITP patients before treatment were significantly higher than those in healthy subjects, and these concentrations were significantly reduced after treatment. The concentration of sPD-1 was positively correlated with the concentration of IFN-γ, and negatively correlated with platelet count. Percentages of PD-1 + CD4 + T cells and PD-L1 + DCs in ITP patients are higher than those in healthy subjects, but elevated sPD-1 concentration in the blood blocks PD-1/PD-L1 signaling pathway, leading to unaffected Th cell function. Elevated concentrations of IFN-γ and IL-17 in the blood may participate in the occurrence and development of ITP.